The influence of sustainable strategic orientations towards sustainable services by third party logistics (3PLS) in closed-Loop Supply chains (CLSCS) / Siti Fatin 'Ainaa Shaikh Mahdzar - Shaikh Mahdzar, Siti Fatin 'Ainaa (Research Management Institute (RMI), 2016)
In the year 2009, the government has put a serious effort in introducing the National Green Technology Policy and National Climate Change with the emphasis on the energy and natural resources conservation also to promote the use of renewable resources. In conjunction to this, the Prime Minister of Malaysia, Dato' Seri Najib Tun Abdul Razak speech during the introductory motion to table the Tenth Malaysia Plan on 10 June 2010 denoted the government's significant efforts towards the green technology applications and sustainability initiatives in Malaysia. Firms see sustainability initiatives as a differentiation strategy towards competitive advantage in the market. Through the recent development and the green innovation, many firms have started to put more emphasis and commitment towards improving environment sustainability by putting a pressure on their suppliers. The aim of this study is to develop an empirical framework on the reputation-based strategy, efficiency-based strategy and innovation-based strategy (sustainable strategic orientations) influenced the sustainable services on the implementation of closed-loop supply chains (CLSCs) by third party logistics (3PLs) to meet the customers' demand. There were 140 respondents gave feedback in this study from the logistics' firms who involved and do not involved in closed-loop supply chains' activities. All of the respondents come from the Penang Freight Forwarders Association (PFFA) Members. The findings showed that there were three dimensions of independent variables. The independent variables are reputation-based strategy, efficiency-based strategy and innovationbased strategy. Among the three independent variables, only efficiency-based strategy showed significant relationship to the sustainable services. However, the reputation-based strategy and innovation-based strategy were no significant relationship to the sustainable services.